Phytoseiid mites (Acari Phytoseiidae) in North-Italian appie orchards: distribution, biology, ecology and economie importance (Bollettino di zoologia agraria e bachicoltura, 2024)
The results of a faunistic survey on predacious mites of the Phytoseiidae family, carried out in appie orchards on northern ltaly (Piemonte, Lombardia, Veneto, Trentino-Alto Adige, Friuli-Venezia Giulia and Emilia-Romagna) are reported. Samples have been especially taken from commerciai orchards, sometimes in different varieties and over three years. Specimens of phytoseiid mites were collected in the greater part of samples. Five species of phytoseiid mites were recorded: Amblyseius andersoni (Chant), Amblyseius finlandicus (Oud.), Amblyseius aberrans (Oud.), Typhlodromus pyri Scheuten and Typhlodromus talbii Athias-Henriot. A. andersoni seems widespread in all the regions while T. pyri is abundant in the northern areas (Trentino-Alto Adige and Lombardia).A review of the most important research works on these species have been reported.
Keywords: apple; Phytoseiidae; distribution; biology; economic importance